2009
DOI: 10.1161/hypertensionaha.108.115154
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Estimates of Hypertension Control From Ambulatory and Clinic Blood Pressure Measurements in Hypertensive Kidney Disease

Abstract: Abstract-Ambulatory blood pressure (ABP) monitoring provides unique information about day-night patterns of blood pressure (BP). The objectives of this article were to describe ABP patterns in African Americans with hypertensive kidney disease, to examine the joint distribution of clinic BP and ABP, and to determine associations of hypertensive target organ damage with clinic BP and ABP. This study is a cross-sectional analysis of baseline data from the African American Study of Kidney Disease Cohort Study. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
225
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 256 publications
(250 citation statements)
references
References 37 publications
19
225
2
4
Order By: Relevance
“…The prevalence of MHT varies considerably among different reports: Ohkubo et al (35). The percentage of MHT in this study was relatively high compared with these previous reports except for the African American Study of Kidney Disease and Hypertension.…”
Section: Discussioncontrasting
confidence: 57%
“…The prevalence of MHT varies considerably among different reports: Ohkubo et al (35). The percentage of MHT in this study was relatively high compared with these previous reports except for the African American Study of Kidney Disease and Hypertension.…”
Section: Discussioncontrasting
confidence: 57%
“…The prevalence of masked hypertension was similar in CRIC participants when compared with other cohorts of patients with CKD, such as in the African American Study of Kidney Disease and Hypertension Cohort Study and the CKD Japan Cohort, at 43% and 31% respectively (9,(27)(28)(29). However, in a meta-analysis by Agarwal et al and a crosssectional study from Spain, masked hypertension was present in less than 10% of CKD patients (30,31).…”
Section: Discussionmentioning
confidence: 63%
“…Earlier studies of CKD cohorts have shown an increased risk for masked and sustained hypertension with elevated urine protein, but analyses were unadjusted or obtained from small cohorts (9,27,33). In CRIC, masked hypertension was associated with low eGFR, and masked and sustained hypertension were associated with elevated urine protein, independent of other risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations